Disparities in minimally invasive surgery for elective inguinal hernia repair across Europe: secondary analysis of an international cohort study - Maria Picciochi; Alberto G Barranquero; Toni Risteski (Oxford University Press (OUP), 2025)
Healthcare systems in Europe vary in funding, accessibility, and spending per capita, potentially influencing patient access to advanced surgical techniques. This study aimed to provide a snapshot of the utilization of minimally invasive surgery for elective inguinal hernia repair across Europe. Methods This was a secondary analysis of an international, prospective observational study of inguinal hernia repairs conducted between 30 January and 21 May 2023. Adults undergoing elective inguinal hernia repair in Europe were included in the present analysis. The four European regions according to the United Nations geoscheme (Southern, Eastern, Northern, and Western Europe) were compared. A multilevel multivariable logistic regression model was used to explore factors associated with use of minimally invasive surgery. Results A total of 8355 patients from 254 hospitals across 23 European countries were included: 5590 from Southern, 587 from Eastern, 1541 from Northern, and 637 from Western Europe. Most hospitals were public (88.8%) and tertiary level (49.9%). Patient and hernia characteristics were generally similar, except Western Europe reported higher rates of bilateral hernias (25.9% versus 14.1% overall). Minimally invasive surgery was performed in 26.0% of patients, 70.6% in Western, 37.9% in Northern, 46.5% in Eastern, and 15.4% in Southern Europe. Multivariable regression showed significant regional disparities. Multivariable regression also identified bilateral hernias (adjusted odds ratio 14.33 (95% confidence interval 11.76 to 17.47), surgeons with experience of ≥ 201 procedures (odds ratio 3.54, 2.75 to 4.54), and private hospitals (odds ratio 2.80, 1.03 to 7.65) as factors associated with greater use of minimally invasive surgery. Conclusion Significant disparities in minimally invasive surgery for elective inguinal hernia repair exist across Europe. Targeted initiatives should especially prioritize Southern Europe to ensure equitable access to advanced techniques.
Keywords: surgical procedures; minimally invasive; hernias; hospitals; private